Internalisasi Nilai-Nilai Pendidikan Islam dalam Meningkatkan Resiliensi Peserta Didik Di SMK Mansyaul Huda - Habibah, Nur Faiz (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The life of every student has a variety of different personal problems. The students' environment that provides examples in every behavior that can be recorded by students then to be followed in the lives of students. Internalization of Islamic has become a key factor in educating educator in their attitudesto get better. This study aims to explain the resilience of students. In this study using a naturalistic qualitative approach, with a location in Mansyaul Huda Vocational high School which is under the Mansyaul Huda Islamic Boarding School Foundation, Kedungasri Village, Tegaldlimo Subdistrict, Banyuwangi Regency. To collect data the method of observation and document analysis are used. In testing the validity of the data measured using triangulation techniques sources, methods, extending the time of observation, checking with colleagues through discussion, and member-check. Data analysis was carried out with steps of data reduction, data display and conclusion making. The diversity of students' problems wichwas balanced with the internalization of Islamic values ​​in education had a significant role in increasing student resilience. Students who gain knowledge about Islamic values ​​are increasingly aware that every problem faced by students has a way that can be done to increase resilience to overcome any problem that he faces. The result of the introduction of Islamic values applied at Mansyaul Huda Vocational high School is experiencing an increase in resilience for students.